Evaluation of the Impacts of Play Activities on the Formation and Development of Cooperative Skills in Preschool Children Aged 5-6 Years: Scientific Evidence from Experimental Study in Vietnam - MINH, VU THI NGOC; HUYEN, NGUYEN THI THANH; NHUNG, CHU THI HONG; GIANG, VU THI HUONG; MY, DAO THI (Journal of Ecohumanism, 2025)
Preschool children’s main activity is playing. This study will use exploratory factor analysis (EFA) and a multiple regression model to assess the impact of play activity elements on the formation and development of cooperative skills in preschool children aged 5-6. According to research findings and scientific evidence, the factors of play activities and cooperative skills for 5-6 year-old preschool children have a strong correlation. This means that play activities have been identified as the primary tools and means of educating, forming, and developing cooperative skills in preschool children aged 5-6. This study also makes recommendations for kindergartens: It is necessary to integrate and mix skill education content with other educational contents so that children’s education can be carried out naturally and effectively through children’s experiences in preschool activities, in order to contribute to the development of psychological functions and comprehensive personality formation for children.